EFFECT OF MOISTURE AND TEMPERATURE ABOUT THERMAL DIFFUSIVITY IN ANDEAN GRAINS - Huamán Castilla, Nils L. (2016)
This study shows a simple method for evaluating the thermal diffusivity (α) in Andean grains quinoa (Chenopodium quinoa Willd) and cañihua (Chenopodium pallidicaule Aellen). In addition the effect of temperature 25 to 35 °C and humidity based humidity 10 to 20% about the behavior of this property was studied. The method used to determine the diffusivity was proposed by Gupta, which makes use of heat penetration curves in specially reinforced equipment for this purpose. The results indicate that the values vary between 7.5 and 8.9 x 10-8 m2 s-1. The evaluation of the data indicates that there is a strong influence on the type of grain, humidity and temperature in this thermal property. Additionally, the response surface methodology was used to find an empirical model to represent the thermal diffusivity depending on the moisture content and temperature.